PENGARUH HARAPAN PENGAJAR TERHADAP MOTIVASI DAN PRESTASI SISWA DI KELAS - Setiadi Umar; Christin . (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
This research refers to the research conducted by Rosenthal and Jacobson (1968), which finds that students' intellectual development is influenced by their teacher expectations and how these expectations are communicated to them. Therefore, this study hypothesizes that positive teacher expectations and behavior in experimental classes for one semester would strengthen students’ effort and motivation in achieving higher performance in the experimental classes. In this experiment, students / respondents were not isolated from external environmental influences, such as from the influence of other their 'regular’ classes, lecturers, as well as their classmates. The method used in this study was experimentation method using two teachers and two subjects. Each teacher taught two classes of one same subject, which were divided into experimental group and control group. The result of this experimentation shows that the students' achievement in both of the experimental classes is not different significantly than those in regular/ control classes.